Acute demyelinating Polyradiculoneuropathy with CSF Pleocytosis under Therapy with BRAF/MEK Inhibitor in advanced malignant Melanoma - Hecker, C.; Madzar, Dominik; Schultz, E.; Debus, D. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Age of epilepsy onset as modulating factor for naming deficit after epilepsy surgery: a voxel-based lesion-symptom mapping study - Reindl, Caroline; Walther, Katrin; Allgäuer, Anna-Lena; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Gollwitzer, Stephanie; Schwarz, Michael; Trollmann, Regina; Madzar, Dominik; Knott, Michael; Dörfler, Arnd; et al. (Scientific Reports, 2023)
Age at onset of epilepsy is an important predictor of deterioration in naming ability following epilepsy surgery. In 141 patients with left hemispheric epilepsy and language dominance who received epilepsy surgery at the Epilepsy Centre Erlangen, naming of objects (Boston naming test, BNT) was assessed preoperatively and 6 months postoperatively. Surgical lesions were plotted on postoperative MRI and normalized for statistical analysis using voxel-based lesion-symptom mapping (VBLSM). The correlation between lesion and presence of postoperative naming deterioration was examined varying the considered age range of epilepsy onsets. The VBLSM analysis showed that volumes of cortex areas in the left temporal lobe, which were associated with postoperative decline of naming, increased with each year of later epilepsy onset. In patients with later onset, an increasing left posterior temporobasal area was significantly associated with a postoperative deficit when included in the resection. For late epilepsy onset, the temporomesial expansion also included the left hippocampus. The results underline that early onset of epilepsy is a good prognostic factor for unchanged postoperative naming ability following epilepsy surgery. For later age of epilepsy onset, the extent of the area at risk of postoperative naming deficit at 6 months after surgery included an increasing left temporobasal area which finally also comprised the hippocampus.
CRIS-Team Scopus Importer:2023-09-08

Amantadine treatment is associated with improved consciousness in patients with non-traumatic brain injury - Ruehl, Lena; Kuramatsu, Joji; Sembill, Jochen; Kallmünzer, Bernd; Madzar, Dominik; Gerner, Stefan; Giede-Jeppe, Antje; Balk, Stefanie; Müller, Tamara; Jäger, Jakob; Schwab, Stefan; Huttner, Hagen; et al. (Journal of Neurology Neurosurgery and Psychiatry, 2022)
Objective This study determined the effect of amantadine treatment on consciousness in patients with non-traumatic brain injury. Methods We pooled individual patient data of five single-centre observational studies to determine the effect of amantadine treatment among patients with ischaemic stroke, intracerebral haemorrhage, subarachnoid haemorrhage, community-acquired bacterial meningitis and status epilepticus, admitted between January 2012 and December 2015 and ventilated >= 7 days. Patient selection and multivariable regression modelling were used to adjust for differences in intergroup comparison and for parameters associated with consciousness. Improvement of consciousness 5 days after treatment initiation was defined as primary outcome. Secondary outcomes included Glasgow Coma Scale (GCS) at day 5 and GCS at day 10, rate of ICU delirium, epileptic seizures and all-cause mortality at 90 days. Results Overall, 84 of 294 (28.6%) eligible patients received amantadine. Amantadine treatment was associated with improvement of consciousness at day 5 (amantadine: 86.9% vs control: 54.0%; absolute difference: 32.9 (20.0-44.2); adjusted OR (aOR): 5.71 (2.50-13.05), p<0.001). Secondary outcomes showed differences in GCS 5 days (9 (8-11) vs 6 (3-9), p<0.001) and GCS 10 days (10(8-11) vs 9(6-11),p=0.003) after treatment initiation. There were no significant differences regarding all-cause mortality (aOR: 0.89 (0.44-1.82), p=0.758) and ICU delirium (aOR: 1.39 (0.58-3.31), p=0.462). Rate of epileptic seizures after initiation of amantadine treatment was numerically higher in the amantadine group (amantadine: 10.7% vs control: 3.0%; absolute difference: 7.7 (0.3-16.4); aOR: 3.68 (0.86-15.71), p=0.079). Conclusions Amantadine treatment is associated with improved consciousness among patients with different types of non-traumatic brain injury in this observational cohort analysis. Epileptic seizures should be considered as potential side effects and randomised controlled trials are needed to confirm these findings.
CRIS-Team WoS Importer:2022-02-11

Author Correction: Guidelines for Neuroprognostication in Adults with Guillain–Barré Syndrome (Neurocritical Care, (2023), 38, 3, (564-583), 10.1007/s12028-023-01707-3) - Busl, Katharina M.; Fried, Herbert; Muehlschlegel, Susanne; Wartenberg, Katja E.; Rajajee, Venkatakrishna; Alexander, Sheila A.; Creutzfeldt, Claire J.; Fontaine, Gabriel V.; Hocker, Sara E.; Hwang, David Y.; Kim, Keri S.; Madzar, Dominik; et al. (Neurocritical Care, 2023)
The original article has been updated to insert the following sentence, before the line “The librarian search string.” in the Systematic Review Methodology paragraph. The in-depth literature search first conducted on February 20, 2019, included literature from 1946 onwards and was last updated on 3/16/2022.
CRIS-Team Scopus Importer:2023-09-29

Correction to: Guidelines for Neuroprognostication in Adults with Guillain–Barré Syndrome (Neurocritical Care, (2023), 10.1007/s12028-023-01707-3) - Busl, Katharina M.; Fried, Herbert; Muehlschlegel, Susanne; Wartenberg, Katja E.; Rajajee, Venkatakrishna; Alexander, Sheila A.; Creutzfeldt, Claire J.; Fontaine, Gabriel V.; Hocker, Sara E.; Hwang, David Y.; Kim, Keri S.; Madzar, Dominik; et al. (Neurocritical Care, 2023)
The original article has been updated to correct Row 2 of Table 4 “04-Jul” to “4–7”.
CRIS-Team Scopus Importer:2023-05-05

Guidelines for Neuroprognostication in Adults with Guillain–Barré Syndrome - Busl, Katharina M.; Fried, Herbert; Muehlschlegel, Susanne; Wartenberg, Katja E.; Rajajee, Venkatakrishna; Alexander, Sheila A.; Creutzfeldt, Claire J.; Fontaine, Gabriel V.; Hocker, Sara E.; Hwang, David Y.; Kim, Keri S.; Madzar, Dominik; et al. (Neurocritical Care, 2023)
Background: Guillain–Barré syndrome (GBS) often carries a favorable prognosis. Of adult patients with GBS, 10–30% require mechanical ventilation during the acute phase of the disease. After the acute phase, the focus shifts to restoration of motor strength, ambulation, and neurological function, with variable speed and degree of recovery. The objective of these guidelines is to provide recommendations on the reliability of select clinical predictors that serve as the basis of neuroprognostication and provide guidance to clinicians counseling adult patients with GBS and/or their surrogates. Methods: A narrative systematic review was completed using Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology. Candidate predictors, including clinical variables and prediction models, were selected based on clinical relevance and presence of appropriate body of evidence. The Population/Intervention/Comparator/Outcome/Time frame/Setting (PICOTS) question was framed as follows: “When counseling patients or surrogates of critically ill patients with Guillain–Barré syndrome, should [predictor, with time of assessment if appropriate] be considered a reliable predictor of [outcome, with time frame of assessment]?” Additional full-text screening criteria were used to exclude small and lower quality studies. Following construction of an evidence profile and summary of findings, recommendations were based on four GRADE criteria: quality of evidence, balance of desirable and undesirable consequences, values and preferences, and resource use. In addition, good practice recommendations addressed essential principles of neuroprognostication that could not be framed in PICOTS format. Results: Eight candidate clinical variables and six prediction models were selected. A total of 45 articles met our eligibility criteria to guide recommendations. We recommend bulbar weakness (the degree of motor weakness at disease nadir) and the Erasmus GBS Respiratory Insufficiency Score as moderately reliable for prediction of the need for mechanical ventilation. The Erasmus GBS Outcome Score (EGOS) and modified EGOS were identified as moderately reliable predictors of independent ambulation at 3 months and beyond. Good practice recommendations include consideration of both acute and recovery phases of the disease during prognostication, discussion of the possible need for mechanical ventilation and enteral nutrition during counseling, and consideration of the complete clinical condition as opposed to a single variable during prognostication. Conclusions: These guidelines provide recommendations on the reliability of predictors of the need for mechanical ventilation, poor functional outcome, and independent ambulation following GBS in the context of counseling patients and/or surrogates and suggest broad principles of neuroprognostication. Few predictors were considered moderately reliable based on the available body of evidence, and higher quality data are needed.
CRIS-Team Scopus Importer:2023-03-31
Keywords: Guillain–Barré syndrome; Outcome; Polyradiculoneuropathy; Prognosis

Guidelines for neuroprognostication in adults with traumatic spinal cord injury - Mahanes, Dea; Muehlschlegel, Susanne; Wartenberg, Katja E.; Rajajee, Venkatakrishna; Alexander, Sheila A.; Busl, Katharina M.; Creutzfeldt, Claire J.; Fontaine, Gabriel V.; Hocker, Sara E.; Hwang, David Y.; Kim, Keri S.; Madzar, Dominik; et al. (Neurocritical Care, 2023)
Background: Traumatic spinal cord injury (tSCI) impacts patients and their families acutely and often for the long term. The ability of clinicians to share prognostic information about mortality and functional outcomes allows patients and their surrogates to engage in decision-making and plan for the future. These guidelines provide recommendations on the reliability of acute-phase clinical predictors to inform neuroprognostication and guide clinicians in counseling adult patients with tSCI or their surrogates. Methods: A narrative systematic review was completed using Grading of Recommendations Assessment, Development, and Evaluation methodology. Candidate predictors, including clinical variables and prediction models, were selected based on clinical relevance and presence of an appropriate body of evidence. The Population/Intervention/Comparator/Outcome/Timing/Setting question was framed as “When counseling patients or surrogates of critically ill patients with traumatic spinal cord injury, should < predictor, with time of assessment if appropriate > be considered a reliable predictor of < outcome, with time frame of assessment >?” Additional full-text screening criteria were used to exclude small and lower quality studies. Following construction of an evidence profile and summary of findings, recommendations were based on four Grading of Recommendations Assessment, Development, and Evaluation criteria: quality of evidence, balance of desirable and undesirable consequences, values and preferences, and resource use. Good practice recommendations addressed essential principles of neuroprognostication that could not be framed in the Population/Intervention/Comparator/Outcome/Timing/Setting format. Throughout the guideline development process, an individual living with tSCI provided perspective on patient-centered priorities. Results: Six candidate clinical variables and one prediction model were selected. Out of 11,132 articles screened, 369 met inclusion criteria for full-text review and 35 articles met eligibility criteria to guide recommendations. We recommend pathologic findings on magnetic resonance imaging, neurological level of injury, and severity of injury as moderately reliable predictors of American Spinal Cord Injury Impairment Scale improvement and the Dutch Clinical Prediction Rule as a moderately reliable prediction model of independent ambulation at 1 year after injury. No other reliable or moderately reliable predictors of mortality or functional outcome were identified. Good practice recommendations include considering the complete clinical condition as opposed to a single variable and communicating the challenges of likely functional deficits as well as potential for improvement and for long-term quality of life with SCI-related deficits to patients and surrogates. Conclusions: These guidelines provide recommendations about the reliability of acute-phase predictors of mortality, functional outcome, American Spinal Injury Association Impairment Scale grade conversion, and recovery of independent ambulation for consideration when counseling patients with tSCI or their surrogates and suggest broad principles of neuroprognostication in this context.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Functional status; Outcome; Prognosis; Spinal cord injuries; Trauma

Guidelines for Neuroprognostication in Comatose Adult Survivors of Cardiac Arrest - Rajajee, Venkatakrishna; Muehlschlegel, Susanne; Wartenberg, Katja E.; Alexander, Sheila A.; Busl, Katharina M.; Chou, Sherry H.Y.; Creutzfeldt, Claire J.; Fontaine, Gabriel V.; Fried, Herbert; Hocker, Sara E.; Hwang, David Y.; Kim, Keri S.; et al. (Neurocritical Care, 2023)
Background: Among cardiac arrest survivors, about half remain comatose 72 h following return of spontaneous circulation (ROSC). Prognostication of poor neurological outcome in this population may result in withdrawal of life-sustaining therapy and death. The objective of this article is to provide recommendations on the reliability of select clinical predictors that serve as the basis of neuroprognostication and provide guidance to clinicians counseling surrogates of comatose cardiac arrest survivors. Methods: A narrative systematic review was completed using Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology. Candidate predictors, which included clinical variables and prediction models, were selected based on clinical relevance and the presence of an appropriate body of evidence. The Population, Intervention, Comparator, Outcome, Timing, Setting (PICOTS) question was framed as follows: “When counseling surrogates of comatose adult survivors of cardiac arrest, should [predictor, with time of assessment if appropriate] be considered a reliable predictor of poor functional outcome assessed at 3 months or later?” Additional full-text screening criteria were used to exclude small and lower-quality studies. Following construction of the evidence profile and summary of findings, recommendations were based on four GRADE criteria: quality of evidence, balance of desirable and undesirable consequences, values and preferences, and resource use. In addition, good practice recommendations addressed essential principles of neuroprognostication that could not be framed in PICOTS format. Results: Eleven candidate clinical variables and three prediction models were selected based on clinical relevance and the presence of an appropriate body of literature. A total of 72 articles met our eligibility criteria to guide recommendations. Good practice recommendations include waiting 72 h following ROSC/rewarming prior to neuroprognostication, avoiding sedation or other confounders, the use of multimodal assessment, and an extended period of observation for awakening in patients with an indeterminate prognosis, if consistent with goals of care. The bilateral absence of pupillary light response > 72 h from ROSC and the bilateral absence of N20 response on somatosensory evoked potential testing were identified as reliable predictors. Computed tomography or magnetic resonance imaging of the brain > 48 h from ROSC and electroencephalography > 72 h from ROSC were identified as moderately reliable predictors. Conclusions: These guidelines provide recommendations on the reliability of predictors of poor outcome in the context of counseling surrogates of comatose survivors of cardiac arrest and suggest broad principles of neuroprognostication. Few predictors were considered reliable or moderately reliable based on the available body of evidence.
CRIS-Team Scopus Importer:2023-03-31
Keywords: Cardiac arrest; Coma; Functional status; Mortality; Prognosis

Guidelines for Neuroprognostication in Critically Ill Adults with Intracerebral Hemorrhage - Hwang, David Y.; Kim, Keri S.; Muehlschlegel, Susanne; Wartenberg, Katja E.; Rajajee, Venkatakrishna; Alexander, Sheila A.; Busl, Katharina M.; Creutzfeldt, Claire J.; Fontaine, Gabriel V.; Hocker, Sara E.; Madzar, Dominik; Mahanes, Dea; et al. (Neurocritical Care, 2023)
Background: The objective of this document is to provide recommendations on the formal reliability of major clinical predictors often associated with intracerebral hemorrhage (ICH) neuroprognostication. Methods: A narrative systematic review was completed using the Grading of Recommendations Assessment, Development, and Evaluation methodology and the Population, Intervention, Comparator, Outcome, Timing, Setting questions. Predictors, which included both individual clinical variables and prediction models, were selected based on clinical relevance and attention in the literature. Following construction of the evidence profile and summary of findings, recommendations were based on Grading of Recommendations Assessment, Development, and Evaluation criteria. Good practice statements addressed essential principles of neuroprognostication that could not be framed in the Population, Intervention, Comparator, Outcome, Timing, Setting format. Results: Six candidate clinical variables and two clinical grading scales (the original ICH score and maximally treated ICH score) were selected for recommendation creation. A total of 347 articles out of 10,751 articles screened met our eligibility criteria. Consensus statements of good practice included deferring neuroprognostication—aside from the most clinically devastated patients—for at least the first 48–72 h of intensive care unit admission; understanding what outcomes would have been most valued by the patient; and counseling of patients and surrogates whose ultimate neurological recovery may occur over a variable period of time. Although many clinical variables and grading scales are associated with ICH poor outcome, no clinical variable alone or sole clinical grading scale was suggested by the panel as currently being reliable by itself for use in counseling patients with ICH and their surrogates, regarding functional outcome at 3 months and beyond or 30-day mortality. Conclusions: These guidelines provide recommendations on the formal reliability of predictors of poor outcome in the context of counseling patients with ICH and surrogates and suggest broad principles of neuroprognostication. Clinicians formulating their judgments of prognosis for patients with ICH should avoid anchoring bias based solely on any one clinical variable or published clinical grading scale.
CRIS-Team Scopus Importer:2023-11-17
Keywords: Cerebral hemorrhage; Counseling; Critical care outcomes; Hemorrhagic stroke; Mortality; Patient outcome assessment; Practice guideline; Prognosis; Shared decision making

Guidelines for Neuroprognostication in Critically Ill Adults with Moderate–Severe Traumatic Brain Injury - Muehlschlegel, Susanne; Rajajee, Venkatakrishna; Wartenberg, Katja E.; Alexander, Sheila A.; Busl, Katharina M.; Creutzfeldt, Claire J.; Fontaine, Gabriel V.; Hocker, Sara E.; Hwang, David Y.; Kim, Keri S.; Madzar, Dominik; Mahanes, Dea; et al. (Neurocritical Care, 2024)
Background: Moderate–severe traumatic brain injury (msTBI) carries high morbidity and mortality worldwide. Accurate neuroprognostication is essential in guiding clinical decisions, including patient triage and transition to comfort measures. Here we provide recommendations regarding the reliability of major clinical predictors and prediction models commonly used in msTBI neuroprognostication, guiding clinicians in counseling surrogate decision-makers. Methods: Using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology, we conducted a systematic narrative review of the most clinically relevant predictors and prediction models cited in the literature. The review involved framing specific population/intervention/comparator/outcome/timing/setting (PICOTS) questions and employing stringent full-text screening criteria to examine the literature, focusing on four GRADE criteria: quality of evidence, desirability of outcomes, values and preferences, and resource use. Moreover, good practice recommendations addressing the key principles of neuroprognostication were drafted. Results: After screening 8125 articles, 41 met our eligibility criteria. Ten clinical variables and nine grading scales were selected. Many articles varied in defining “poor” functional outcomes. For consistency, we treated “poor” as “unfavorable”. Although many clinical variables are associated with poor outcome in msTBI, only the presence of bilateral pupillary nonreactivity on admission, conditional on accurate assessment without confounding from medications or injuries, was deemed moderately reliable for counseling surrogates regarding 6-month functional outcomes or in-hospital mortality. In terms of prediction models, the Corticosteroid Randomization After Significant Head Injury (CRASH)-basic, CRASH-CT (CRASH-basic extended by computed tomography features), International Mission for Prognosis and Analysis of Clinical Trials in TBI (IMPACT)-core, IMPACT-extended, and IMPACT-lab models were recommended as moderately reliable in predicting 14-day to 6-month mortality and functional outcomes at 6 months and beyond. When using “moderately reliable” predictors or prediction models, the clinician must acknowledge “substantial” uncertainty in the prognosis. Conclusions: These guidelines provide recommendations to clinicians on the formal reliability of individual predictors and prediction models of poor outcome when counseling surrogates of patients with msTBI and suggest broad principles of neuroprognostication.
CRIS-Team Scopus Importer:2024-03-01
Keywords: Neurocritical care; Outcome; Prognosis; Prognostication; Traumatic brain injury

Meningitis and intracranial abscess due to Mycoplasma pneumoniae in a B cell-depleted patient with multiple sclerosis - Madžar, Dominik; Nickel, Florian; Rothhammer, Veit; Gölitz, Philipp; Geißdörfer, Walter; Dumke, Roger; Lang, Roland (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Mycoplasma pneumoniae, a frequent respiratory pathogen, can cause neurological disease manifestations. We here present a case of M. pneumoniae as cause of meningitis and occurrence of an intracranial abscess as a complication of mastoiditis with septic cerebral venous sinus thrombosis in a patient with multiple sclerosis on anti-CD20 therapy.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Abscess; Anti-CD20 antibody; Complication; Mastoiditis; Multiple sclerosis; Mycoplasma pneumoniae; Ocrelizumab; Rituximab; Septic cerebral venous sinus thrombosis

Phenobarbital in super-refractory status epilepticus (PIRATE): A retrospective, multicenter analysis - Kunst, Stefan; Rojo, Mikel L.; Schmidbauer, Moritz O.; Pelz, Johann; Mueller, Annekatrin; Minnerup, Jens; Meyer, Lennart; Madžar, Dominik; Reindl, Caroline; Madlener, Marie; Malter, Michael; Neumann, Bernhard; et al. (Epilepsia, 2023)
Objective: Super-refractory status epilepticus (SRSE) is an enduring or recurring SE after 24 h or more of general anesthesia. This study aimed to evaluate the efficacy and safety of phenobarbital (PB) for the treatment of SRSE.
CRIS-Team WoS Importer:2023-05-12

Quantitative EEG may predict weaning failure in ventilated patients on the neurological intensive care unit - Welte, Tamara; Gabriel, Maria; Hopfengaertner, Ruediger; Rampp, Stefan; Gollwitzer, Stephanie; Lang, Johannes; Stritzelberger, Jenny; Reindl, Caroline; Madzar, Dominik; Sprügel, Maximilian; Huttner, Hagen; Kuramatsu, Joji; et al. (Scientific Reports, 2022)
Neurocritical patients suffer from a substantial risk of extubation failure. The aim of this prospective study was to analyze if quantitative EEG (qEEG) monitoring is able to predict successful extubation in these patients. We analyzed EEG-monitoring for at least six hours before extubation in patients receiving mechanical ventilation (MV) on our neurological intensive care unit (NICU) between November 2017 and May 2019. Patients were divided in 2 groups: patients with successful extubation (SE) versus patients with complications after MV withdrawal (failed extubation; FE), including reintubation, need for non-invasive ventilation (NIV) or death. Bipolar six channel EEG was applied. Unselected raw EEG signal underwent automated artefact rejection and Short Time Fast Fourier Transformation. The following relative proportions of global EEG spectrum were analyzed: relative beta (RB), alpha (RA), theta (RT), delta (RD) as well as the alpha delta ratio (ADR). Coefficient of variation (CV) was calculated as a measure of fluctuations in the different power bands. Mann–Whitney U test and logistic regression were applied to analyze group differences. 52 patients were included (26 male, mean age 65 ± 17 years, diagnosis: 40% seizures/status epilepticus, 37% ischemia, 13% intracranial hemorrhage, 10% others). Successful extubation was possible in 40 patients (77%), reintubation was necessary in 6 patients (12%), 5 patients (10%) required NIV, one patient died. In contrast to FE patients, SE patients showed more stable EEG power values (lower CV) considering all EEG channels (RB: p < 0.0005; RA: p = 0.045; RT: p = 0.045) with RB as an independent predictor of weaning success in logistic regression (p = 0.004). The proportion of the EEG frequency bands (RB, RA RT, RD) of the entire EEG power spectrum was not significantly different between SE and FE patients. Higher fluctuations in qEEG frequency bands, reflecting greater fluctuation in alertness, during the hours before cessation of MV were associated with a higher rate of complications after extubation in this cohort. The stability of qEEG power values may represent a non-invasive, examiner-independent parameter to facilitate weaning assessment in neurocritical patients.
CRIS-Team Scopus Importer:2022-05-20

Resection of dominant fusiform gyrus is associated with decline of naming function when temporal lobe epilepsy manifests after the age of five: A voxel-based lesion-symptom mapping study - Reindl, Caroline; Allgäuer, Andrea; Kleiser, Benedict; Onugoren, Müjgan Dogan; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Winder, Klemens; Schwarz, Michael; Gollwitzer, Stephanie; Trollmann, Regina; Rösch, Julie; et al. (NeuroImage: Clinical, 2022)
Objective: To determine patients’ characteristics and regions in the temporal lobe where resections lead to a decline in picture naming. Methods: 311 patients with left hemispheric dominance for language were included who underwent epilepsy surgery at the Epilepsy Center of Erlangen and whose picture naming scores (Boston Naming Test, BNT) were available preoperatively and 6-months postoperatively. Surgical lesions were mapped to an averaged template based on preoperative and postoperative MRI using voxel-based lesion-symptom mapping (VBLSM). Postoperative brain shifts were corrected. The relationship between lesioned brain areas and the presence of a postoperative naming decline was examined voxel-wise while controlling for effects of overall lesion size at first in the total cohort and then restricted to temporal lobe resections. Results: In VBLSM in the total sample, a decline in BNT score was significantly related to left temporal surgery. When only considering patients with left temporal lobe resections (n = 121), 40 (33.1%) significantly worsened in BNT postoperatively. VBLSM including all patients with left temporal resections generated no significant results within the temporal lobe. However, naming decline of patients with epilepsy onset after 5 years of age was significantly associated with resections in the left inferior temporal (extent of BNT decline range: 10.8− 14.4%) and fusiform gyrus (decline range: 12.1−18.4%). Significance: Resections in the posterior part of the dominant fusiform and inferior temporal gyrus was associated with a risk of deterioration in naming performance at six months after surgery in patients with epilepsy onset after 5 years of age but not with earlier epilepsy onset.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Basal temporal language area; Epilepsy surgery; Gyrus fusiformis; Lesion localization; Naming; Neuropsychological outcome

Sollte man nicht konvulsive Anfälle und den nicht konvulsiven Status epilepticus auf der Intensivstation aggressiv behandeln: Eine Debatte - Madzar, Dominik; Hamer, Hajo (Klinische Neurophysiologie, 2020)
CRIS-Team Scopus Importer:2021-04-19

Spectral properties of bursts in therapeutic burst suppression predict successful treatment of refractory status epilepticus - Gollwitzer, Stephanie; Hopfengärtner, Rüdiger; Rampp, Stefan; Welte, Tamara; Madžar, Dominik; Lang, Johannes; Reindl, Caroline; Stritzelberger, Jenny; Köhn, Julia; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen B.; et al. (Epilepsy and Behavior, 2024)
Burst suppression (BS) on EEG induced by intravenous anesthesia (IVAT) is standard therapy for refractory status epilepticus (RSE). If BS has any independent therapeutic effect on RSE is disputed. We aimed to define EEG characteristics of BS predicting termination or recurrence of status after weaning. All RSE patients treated with IVAT while undergoing continuous EEG monitoring on the neurological intensive care unit between 2014 and 2019 were screened for inclusion. A one hour-period of visually preselected BS-EEG was analyzed. Bursts were segmented by a special thresholding technique and underwent power spectral analysis. Out of 48 enrolled patients, 25 (52.1 %) did not develop seizure recurrence (group Non SE) after weaning from IVAT; in 23 patients (47.9 %), SE reestablished (group SE). In group Non SE, bursts contained higher amounts of EEG delta power (91.59 % vs 80.53 %, p < 0.0001), while faster frequencies were more pronounced in bursts in group SE (theta: 11.38 % vs 5.41 %, p = 0.0008; alpha: 4.89 % vs 1.82 %, p < 0.0001; beta: 3.23 % vs 1.21 %, p = 0.0002). Spectral profiles of individual bursts closely resembled preceding seizure patterns in group SE but not in group Non SE. Accordingly, persistence of spectral composition of initial ictal patterns in bursts, suggests ongoing SE, merely interrupted but not altered by BS. Fast oscillations in bursts indicate a high risk of status recurrence after weaning from IVAT. EEG guided individualized sedation regimes might therefore be superior to standardized anesthesia protocols.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Intravenous anesthesia; Multimodal monitoring; Quantitative EEG

Status epilepticus-Detection and treatment in the intensive care unit - Reindl, Caroline; Madzar, Dominik; Hamer, Hajo (Der Nervenarzt, 2022)
Status epilepticus is characterized by persistent or repetitive seizures which, without successful treatment, can lead to neuronal damage, neurological deficits and death of the patient. While status epilepticus with motor symptoms can usually be clinically diagnosed, nonconvulsive status epilepticus is often clinically overlooked due to its ambiguous semiology, so that electroencephalography (EEG) recording is necessary. The treatment of status epilepticus is performed in four treatment steps, whereby a difficult to treat status epilepticus is present from the third step at the latest and intensive medical care of the patient is necessary. Timely initiation of treatment and sufficient dosage of anticonvulsive medication are decisive for the success of treatment. There is little evidence for the "late " stages of treatment. Intensive medical measures pose the risk of complications that worsen the prognosis. Especially in nonconvulsive status epilepticus, the use of anesthetics must be weighed against possible complications of mechanical ventilation.
CRIS-Team WoS Importer:2023-01-13

Status epilepticus in patients with glioblastoma: Clinical characteristics, risk factors, and epileptological outcome - Stritzelberger, Jenny; Gesmann, Anna; Fuhrmann, Imke; Balk, Stefanie; Reindl, Caroline; Madzar, Dominik; Uhl, Martin; Welte, Tamara; Brandner, Sebastian; Eisenhut, Felix; Dörfler, Arnd; Coras, Roland; et al. (Seizure-European Journal of Epilepsy, 2023)
Purpose: Epilepsy is a common comorbidity in patients with glioblastoma, however, clinical data on status epilepticus (SE) in these patients is sparse. We aimed to investigate the risk factors associated with the occurrence and adverse outcomes of SE in glioblastoma patients. Methods: We retrospectively analysed electronic medical records of patients with de-novo glioblastoma treated at our institution between 01/2006 and 01/2020 and collected data on patient, tumour, and SE characteristics. Results: In the final cohort, 292/520 (56.2 %) patients developed seizures, with 48 (9.4 % of the entire cohort and 16.4 % of patients with epilepsy, PWE) experiencing SE at some point during the course of their disease. SE was the first symptom of the tumour in 6 cases (1.2 %) and the first manifestation of epilepsy in 18 PWE (6.2 %). Most SE episodes occurred postoperatively (n = 37, 77.1 %). SE occurrence in PWE was associated with postoperative seizures and drug-resistant epilepsy. Adverse outcome (in-house mortality or admission to palliative care, 10/48 patients, 20.8 %), was independently associated with higher status epilepticus severity score (STESS) and Charlson Comorbidity Index (CCI), but not tumour progression. 32/48 SE patients (66.7 %) were successfully treated with first- and second-line agents, while escalation to third-line agents was successful in 6 (12.5 %) cases. Conclusion: Our data suggests a link between the occurrence of SE, postoperative seizures, and drug-resistant epilepsy. Despite the dismal oncological prognosis, SE was successfully treated in 79.2 % of the cases. Higher STESS and CCI were associated with adverse SE outcomes.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Glioblastoma; Status epilepticus; Status epilepticus severity score (STESS)

Value of initial C-reactive protein levels in status epilepticus outcome prediction - Madzar, Dominik; Reindl, Caroline; Mrochen, Anne; Hamer, Hajo; Huttner, Hagen (Epilepsia, 2021)
The role of neuroinflammation in the pathophysiology of seizures is increasingly recognized, and the evaluation of potential biochemical markers of inflammatory processes in seizures and status epilepticus (SE), such as C-reactive protein (CRP), has gained attention. The present study assessed the first CRP level obtained in an SE episode regarding its value for SE outcome prediction. Among 362 admissions for SE during the study period, 231 episodes satisfied the inclusion criteria. Higher initial CRP concentrations were independently associated with in-hospital mortality and poor functional outcome at discharge in logistic regression models adjusting for SE severity, severity of SE etiology, and development of treatment refractoriness. Therefore, initial CRP levels may add to the prediction of SE prognosis. The pathomechanisms through which CRP is linked with the prognosis of SE, however, remain to be established.
CRIS-Team Scopus Importer:2021-03-05
Keywords: acute phase proteins; C-reactive protein; inflammation; laboratory parameters; outcome; status epilepticus

Woman with sudden-onset speech difficulties. - To, Vi Tuong Daniel; Marterstock, Dominique; Madžar, Dominik (Journal of the American College of Emergency Physicians Open, 2023)
EVALuna2:540367